GENWEB : An AI-Powered Platform For Intuitive Prompt-To-Website Generation - Kagajwala, Aliasgar S.; Wagde, Tanvi; Kambe, Ruchika; Lokhande, Pracheta; Wagh , Pooja (International Journal on Advanced Computer Engineering and Communication Technology, 2025)
In today’s digital-first world, a strong online presence has become essential for individuals, creators, and businesses alike. Yet, despite countless website-building platforms such as Wix, Squarespace, and WordPress, creating a unique and personalized website remains a challenge for many. These platforms, while simplifying web development, still confine users within rigid templates and limited customization options. For someone without coding knowledge, translating a creative vision into a functional, aesthetic website often demands either expensive professional help or frustrating hours of trial and error. This persistent gap between imagination and execution highlights a major barrier the knowledge dependency of web creation. To address this challenge, Gen-Web introduces a new paradigm of website generation powered by artificial intelligence and intent-based design. Instead of choosing from predefined templates, users simply describe their vision in natural language for example, “I want a modern, dark-themed portfolio with a hero section, about page, and project gallery.” Gen-Web interprets this request, understands the intent, and constructs a fully functional, responsive website in real-time. Built using Next.js, Tailwind CSS, and LLM-based code synthesis, the system merges human creativity with machine intelligence. At its core, Gen-Web employs transformer-based models that analyze prompts, identify relevant components, and generate clean, modular code. Through Chain-of-Thought prompting and structured backend orchestration, it ensures logical flow, design coherence, and precise alignment with user intent. The entire process, from prompt input to live rendering and iterative refinement, is intuitive, fast, and adaptive. By bridging the gap between creativity and technology, GenWeb democratizes digital creation. It empowers anyone regardless of technical background to build personalized websites effortlessly, transforming the process of web development from a technical skill into a creative expression.